The philosophy of the world of work in the 21st century (2017)
This first project research product on the future of work within the framework of the ILO centenary analyzes from the philosophical perspective the world of work in the twenty-first century as well as the reasons why the labor protectionism that arose from the New Deal and of the creation of the ILO must continue with a re-reading of social justice that allows to transfer the protectionism of subordinate work to the whole world of work. For the above, three major aspects will be addressed: the labor market as part of the economic models generated by societies; the concept of work and its changes in the time product of technologies; and social justice as a principle in the construction of labor law and its re-reading in the twenty-first century. © 2017, Corporacion Universitaria Republicana. All rights reserved.